Hallmarks of aging and immunosenescence: Connecting the dots. (June 2021) - Rodrigues, Leane Perim; Teixeira, Vitória Rodrigues; Alencar-Silva, Thuany; Simonassi-Paiva, Bianca; Pereira, Rinaldo Wellerson; Pogue, Robert; Carvalho, Juliana Lott
Graphical abstract: Highlights: Hallmarks of aging have been poorly characterized in the immune system elements. Immunosenescence, the immune system aging, leads to disease and further senescence. The aged immune system is characterized by altered cell function and systemic cytokine levels. Immunosenescence may be an actionable target to promote healthy aging. Abstract: Aging is a natural physiological process that features various and variable challenges, associated with loss of homeostasis within the organism, often leading to negative consequences for health. Cellular senescence occurs when cells exhaust the capacity to renew themselves and their tissue environment as the cell cycle comes to a halt. This process is influenced by genetics, metabolism and extrinsic factors. Immunosenescence, the aging of the immune system, is a result of the aging process, but can also in turn act as a secondary inducer of senescence within other tissues. This review aims to summarize the current state of knowledge regarding hallmarks of aging in relation to immunosenescence, with a focus on aging-related imbalances in the medullary environment, as well as the components of the innate and adaptive immune responses. Aging within the immune system alters its functionality, and has consequences for the person's ability to fight infections, as well as for susceptibility to chronic diseases such as cancer and cardiovascular disease. The senescence-associated secretory phenotype is described, as well as the involvement of this phenomenon in the paracrine induction of senescence in otherwise healthy cells. Inflammaging is discussed in detail, along with the comorbidities associated with this process. A knowledge of these processes is required in order to consider possible targets for the application of senotherapeutic agents - interventions with the potential to modulate the senescence process, thus prolonging the healthy lifespan of the immune system and minimizing the secondary effects of immunosenescence.